Tarea extraclase de los estudiantes de octavo año de educación general básica paralelos k, l y m del colegio nacional Nueve de Octubre de Machala. 2013 - 2014 - Picón Barreto, Yolanda Estefanía (2014)
On lines and subsequent pages an investigation into student assignments extraclase eighth year of basic education parallel k , l and m October Nine Machala National College is presented , which is particularly important considering that they are a complement very important in the teaching-learning process . The first part of this work includes theoretical and scientific guidelines that support the theoretical framework, which the reason for study- variables extraclase tasks and teaching- learning- emerge to support research based on concepts, definitions and educational contributions they will allow viable working with scientific arguments. In the second part of the report of the research field, which corresponds to the work itself is presented. This section details the quantitative qualitatively investigated, allowing checking the hypotheses and establishing findings and recommendations for lenificar previously diagnosed the problem. Workshop: "Learning to learn” aimed at teachers and students, as an alternative to improve the performance in class and school performance of students in 8th grade Basic General Education " Finally the proposed intervention , entitled arises. This is the substance of the research work, because the strategies and activities that made the authors of this thesis to mitigate the problem under study , first as a contribution to the school where it was designed to do the job field , and secondly , to demonstrate their professional competence , considering that the thesis is the first personal contribution they make it as educational psychologists and vocational counsellors.